An EMG-driven model to investigate cocontraction of lower extremity muscles during gait. - Karakostas T (Emg-driven Model to Investigate Cocontraction of Lower Extremity Muscles During Gait, 2001)
A great challenge for the study of human motion is the development of accurate, non-invasive methods to calculate individual force-time histories during movement. In medicine, for many surgical decisions, muscle balance requires precise definition to avoid serious physician-caused errors. It was the purpose, therefore, of this study to introduce an EMG-driven neuromusculoskeletal model to predict cocontraction among individual musculotendon units that comprise the synergistic and antagonistic muscle groups involved in knee flexion/extension and ankle plantar/dorsi flexion during normal walking gait.Description of the muscle's mechanical response was based on Hill's and Zajac's work, but incorporated individual muscle length, velocity, and excitation considerations for muscle contractions. Processed EMG represented the neural input to the muscle. A musculoskeletal model defining joint kinematics, muscle line of action and architecture of the left lower limb musculotendon units was developed by using SIMM and modifying its associated model. Muscle kinematics were then calculated in conjunction with three dimensional motion data. Computer simulations combined with a calibration procedure allowed the estimation of all model parameters.Individual muscle force profiles were predicted for selected muscles of the lower limb using three subjects during normal walking. Model validation was performed against estimated net joint moments from inverse dynamics.Estimated gains were within physiological range, and a good match was obtained between moment curves. Correlations ranged from 0.73 to 0.97 for the gait trials and RMS differences between 22.2 and 12.99 Nm for the knee and ankle joints individually. Expressed relative to the peak measured moments during gait, the RMS differences ranged from 13.71 to 15.33 percent at the ankle, and 24.95 to 45.58 percent at the knee. The results were similar or better than those previously reported. Cocontraction indexes were higher during events in the gait cycle that required stability and control at the joint.This model provides a solid foundation for further improvements that are discussed. The results support the feasibility of using the proposed model, as a potential solution to the interdeterminancy problem providing solutions to muscle forces involved in normal human movement, and a cocontraction index to assess muscle balance during gait.